DAISY and JOSEPHINE - Gilbert, Melissa, 1964-; Kuo, Julia (New York : Simon & Schuster Books for Young Readers, 2014)
Six-year-old Daisy loves traveling the world with her father, a famous entertainer, and her teacher, Mrs. Minniear, but is lonely until her father brings home Josephine, a French bulldog that speaks and has great fashion sense.
Keywords: Children's stories, English; Fathers and daughters -- Juvenile fiction; Single-parent families -- Juvenile fiction; Loneliness -- Juvenile fiction